1981
DOI: 10.1107/s0567739481001721
|View full text |Cite
|
Sign up to set email alerts
|

Silicon-crystal rocking curves under X-ray acoustic resonance conditions

Abstract: Silicon-crystal rocking curves are measured with a high angular resolution (~0.1") under conditions of the Borrmann effect resonant suppression by transverse ultrasonic vibrations. It is shown that on the curves deep minima appear whose positions depend on the vibrational frequency, in agreement with the theory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
2

Year Published

1983
1983
1998
1998

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(17 citation statements)
references
References 11 publications
0
15
0
2
Order By: Relevance
“…In the present work, use was made of the method of Entin & Assur (1981;Assur & Entin, 1982), analogous to the method developed by Cusatis, Hart & Siddons (1983) (see Fig. 1).…”
Section: Experimental and Resultsmentioning
confidence: 99%
“…In the present work, use was made of the method of Entin & Assur (1981;Assur & Entin, 1982), analogous to the method developed by Cusatis, Hart & Siddons (1983) (see Fig. 1).…”
Section: Experimental and Resultsmentioning
confidence: 99%
“…Consequently, the satellite contribution to the diffraction intensity AI-A691 increases proportionally with w (Entin & Assur, 1981). This effect was used to measure a weak acoustic field (Hw<< 1) in acoustooptical devices integrated on a silicon substrate (Zolotoyabko, Jacobsohn, Shechtman, Kantor & Salzman, 1992 (Zolotoyabko, 1992).…”
Section: A6) = Ak/h= Ij(hw)aoomentioning
confidence: 99%
“…In the case of a perfect crystal, US-induced interaction between the X-ray waves leads to the creation of new gaps on the dispersion surface, Ak,, and, consequently, to the formation of angular satellites in the diffraction spectrum, owing to coherent scattering on the acoustic superlattice (Kohler, Mohling & Peibst, 1974;Entin & Assur, 1981;Chapman, Colella & Bray, 1983). The angular width of the nth-order satellite is expressed as…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that the effect of an ultrasonic wave (USW) on X-ray diffraction is particularly strong for high-frequency acoustic vibrations with spatial wavelengths equal to or greater than the extinction length for the excited reflection (the condition of X-ray acoustic resonance) (Entin, 1977). Previous studies have demonstrated that high-frequency USW excitations in a perfect crystal cause satellites to appear in the diffraction angular spectrum, leading to a broadening of the rocking curve and an increase in the integrated diffraction intensity (K6hler et at, 1970;Entin & Assur, 1981;Chapman etal., 1983). The USW was also shown to be useful in the characterization of crystal imperfection by X-ray diffraction (Zolotoyabko et al, 1992) and for the design of synchrotron monochromators with adjustable reflectivity (Polikarpov et al, 1994;Liss et al, 1997).…”
Section: Introductionmentioning
confidence: 99%